Banjar Laba Nangga, Identifying Stakeholders for Cultural Heritage Management at a Prehistoric Site in North Bali - Westerlaken, Rodney (an1mage, 2016)
Cultural Heritage Management (CHM) defines how stakeholders should deal with their inheritance, whether coming directly from their bloodline, or give by ancestors 2000 years ago. To be able to understand the implications of cultural heritage management one must identify the different stakeholders. In this article a description is given of this process of identifying and all the issues that may rise while identifying stakeholders. Values, beliefs and traditions of different stakeholders and subsequently with different interests get mixed with emotions. This subsequently leads to a loss of scientific research and a just interpretation of what has been found, as in the described case study of Banjar Laba Nangga.